PENINGKATAN MINAT D AN KETERAMPILAN MENULIS TEKS EKSPOSISI TENTANG SENI PERTUNJUKAN JAWA MELALUI METODE MIND MAPPING PADA SISWA KELAS XI MIA 9 SMA NEGERI 1 KARANGANYAR TAHUN AJARAN 2014/2015 - Niken Estirohmawati; Raheni Suhita; Atikah Anindyarini (Universitas Sebelas Maret, 2018)
This research is a classroom action research that is aimed to improve interest and writing skill in writing exposition about Javanese performing art using mind mapping method in XI MIA 9 students of SMA Negeri 1 Karanganyar. This research was conducted in two cycles, each cycle consists of planning, acting, observing and reflecting. The subject of this action research is students of class XI MIA 9 SMA Negeri 1 Karanganyar and a teacher in the learning process. The source of the data was obtained from informant (students and teachers), places and event, and documents. The technique of collecting data that is used was interview, observation and document analysis. The validity test was using triangulation method and data. The method of data analysis was using qualitative descriptive analysis and descriptive comparative analysis. Based on the research, concluded that the application of mind mapping methods can increase student interest. This can be demostrated by the observation of the average activity in the first cycle at 69 with sufficient criteria and increased to 83.5 in the second cycle with the criteria very well. Secondly, mind mapping method can improve the writing skills of exposition text. Whereas, in the case of writing skill in writing exposition text, the amount of the students that passed in pre-research were 32% students, while the amount of the students that did not passed is 68% students. After the treatment is implemented in cycle I, the amount of the students that passed was 71% students and 29% students did not passed. Furthermore, in cycle II 87% students passed. The conclusion of this research is the implementation of mind mapping method can improve learning interest and writing skill in writing exposition text.